2007
DOI: 10.1007/s10815-007-9162-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on DNA fragmentation, chromatin packaging and conventional semen parameters in spermatozoa of oligoasthenoteratozoospermic patients

Abstract: Purpose To investigate the effects of male ageing on DNA fragmentation and chromatin packaging in the spermatozoa of oligoasthenoteratozoospermic (OAT) patients. Methods Sixty-one OAT patients and 49 men with proven fertility (controls) were included in the present study. DNA fragmentation was detected by terminal deoxynucleotidyl transferase-mediated dUTP-nick end labelling (TUNEL) assay, while chromatin packaging was assessed by chromomycin A 3 (CMA 3 ) staining. Results In the patient group, semen volume, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 47 publications
13
52
3
2
Order By: Relevance
“…Using the TUNEL assay, we did not found a significant association between the paternal age and the levels of DNA fragmentation in infertile and fertile men. Using the same technique, our findings are in accordance with the data of Colin et al [10] and in discordance with the results of Vagnini et al [6] and Plastira et al [29] who reported that male aging affects the chromatin integrity of spermatozoa, but only in infertile population. Using a different assay for measuring DNA strand damage in sperm, the SCSA which measures the susceptibility of sperm DNA to in situ acid induced denaturation, Spano et al [7] found a strong association of DNA fragmentation index with age among men 18-55 years olds.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Using the TUNEL assay, we did not found a significant association between the paternal age and the levels of DNA fragmentation in infertile and fertile men. Using the same technique, our findings are in accordance with the data of Colin et al [10] and in discordance with the results of Vagnini et al [6] and Plastira et al [29] who reported that male aging affects the chromatin integrity of spermatozoa, but only in infertile population. Using a different assay for measuring DNA strand damage in sperm, the SCSA which measures the susceptibility of sperm DNA to in situ acid induced denaturation, Spano et al [7] found a strong association of DNA fragmentation index with age among men 18-55 years olds.…”
Section: Discussionsupporting
confidence: 82%
“…A significant age-dependent decrease [2,25] as well as constant values over the age range [19] or even a non significant age dependent increase with age [26] have been detected in healthy men. In infertile patient's sperm concentration remains unalterated [22] or increases [21,23,[26][27][28][29]. In our study we had found that sperm concentration increases with age in infertile men but remains constant in fertile men.…”
Section: Discussionsupporting
confidence: 46%
“…It is important to highlight that in the PR group, we observed a high mean paternal age (40.6 ± 5.6 years), which has been previously demonstrated to be associated with a decline in semen quality [34], the presence of sperm vacuoles [35], lower proportion of sperm with normal morphologies and higher DNA fragmentation rate. Therefore, the paternal age influence on the findings must not be disregarded.…”
Section: Discussionmentioning
confidence: 52%
“…Two further studies based on the TUNEL assay provided more coherent results. Both groups reported that male aging affects the chromatin integrity of spermatozoa, but only in infertile populations [25,26]. The modified Nicoletti assay, used in our study, is based on the long incubation time of 16-24 h, during which the DNA fragments diffuse to the extracellular medium, since the plasma membrane has been perforated by Triton-X and Na-citrate.…”
Section: Discussionmentioning
confidence: 98%